1992
DOI: 10.1111/j.1365-2788.1992.tb00488.x
|View full text |Cite
|
Sign up to set email alerts
|

Living in hospital and hostel: the pattern of interactions of people with learning difficulties

Abstract: ABSTRACT. This study compared interactions between the staff and residents living in hospital wards and in community‐based hostels. Twenty‐four people with moderate to severe learning difficulties participated in this study. Interactions were categorized according to who was the initiator and recipient, their purpose, attitude of the recipient, duration, and place. It was found that the hospital and hotel residents had virtually no interactions with people outwith the establishment in which they lived. The ho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 8 publications
1
10
0
Order By: Relevance
“…Given the research findings detailing the limited number of interactions that typically occur between staff and residents in residential services (Felce, Lowe, & Blackman, 1995;Felce & Perry, 1995;Hundert, Walton-Allen, Vasdev, Cope, & Summers, 2003;Markova, Jahoda, Cattermole, & Woodward, 1992), it is not surprising to find a body of recent research that is dedicated to changing and improving interactions between residents and the staff who support them. These studies include staff training programs (Chatterton, 1999;Dobson et al, 2002;McLeod, Houston, & Seyfort, 1996;Money, 1997), activity scheduling, direct skill teaching to residents (Sigafoos et al, 2004), and staff management procedures (Seys & Duker, 1993;Suda & Miltenberger, 1993).…”
Section: Staff Training Programsmentioning
confidence: 96%
“…Given the research findings detailing the limited number of interactions that typically occur between staff and residents in residential services (Felce, Lowe, & Blackman, 1995;Felce & Perry, 1995;Hundert, Walton-Allen, Vasdev, Cope, & Summers, 2003;Markova, Jahoda, Cattermole, & Woodward, 1992), it is not surprising to find a body of recent research that is dedicated to changing and improving interactions between residents and the staff who support them. These studies include staff training programs (Chatterton, 1999;Dobson et al, 2002;McLeod, Houston, & Seyfort, 1996;Money, 1997), activity scheduling, direct skill teaching to residents (Sigafoos et al, 2004), and staff management procedures (Seys & Duker, 1993;Suda & Miltenberger, 1993).…”
Section: Staff Training Programsmentioning
confidence: 96%
“…(2002) classified the friendships of young people with Down syndrome (12‐ to 24‐year olds), into three levels of increasing intimacy, and concluded that in only five cases (25% of those concerned) could the friendship be said to reach the highest level (friendship as mutual trust and assistance). Markova et al. (1992) also report a low level of interaction between even those in hostels and members of the wider community.…”
Section: Introductionmentioning
confidence: 95%
“…2001). Unfortunately, paid workers have been observed to provide limited opportunities for social interaction (Hile & Walbran 1991; Markova et al. 1992; Schepsi & Reid 1994).…”
Section: Introductionmentioning
confidence: 99%
“…1992; Schepsi & Reid 1994). Interactions in congregate care have been described as brief and infrequent, comprising mostly instructions (Hile & Walbran 1991; Markova et al. 1992; Schepsi & Reid 1994).…”
Section: Introductionmentioning
confidence: 99%